Identification of Distribution Channels to Create Sustainable Vegetable Prices - Aflit Nuryulia Praswati; Bayu Dian Aji (Indonesian Journal of Sustainability Accounting and Management, 2017)
The price of vegetables has a role as a contributor to the rate of inflation. Currently the number of vegetable production in Boyolali region can no longer meet the needs of local communities. The limited amount of vegetable production and the inhibition of the vegetable distribution channel creates a scarcity of vegetables that result in price increases. This study aims to identify the distribution channel and the formation of vegetable prices derived from Boyolali area. The method used in this research is quantitative and qualitative. Respondents from this study consisted of farmers, wholesalers, small trader and end consumers. The type of distribution channel prevailing in Boyolali area are traditional and modern distribution channels. Intermediate distribution channels play a greater role in determining vegetable prices. If farmers want to improve their economic condition, it needs innovation and creativity in the process of planting, harvesting, packaging and marketing vegetable products.